Pengaruh Penggunaan Alat Peraga Funny Block terhadap Pemahaman Materi Bangun Ruang Balok Siswa Kelas VI SD - Alia Nurul Komariah; Alifa Nur Renita; Gisni Siti Nuraeni; Putri Nurasyifa Ariana Herawati; Hetty Patmawati; Sandy Ihsan Amarulloh (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
This study aims to analyze the impact of using Funny Block teaching aids on sixth-grade elementary school students’ understanding of rectangular prism geometry. The primary issue faced by students is the difficulty in grasping abstract spatial concepts when learning is conducted only theoretically. This research employs a quantitative method with an experimental design. Sixty students were divided into two groups: the first group was taught conventionally, while the second group used Funny Block teaching aids. Data were collected through short essay tests and analyzed using t-tests and the Mann-Whitney U test. The results show that the average test score of the Funny Block group was higher than the conventional group. The Mann-Whitney U test revealed a statistically significant difference. Students using Funny Blocks demonstrated better visualization skills, particularly for problems requiring spatial comprehension. This teaching aid effectively supports students in understanding abstract concepts concretely, improving accuracy and efficiency in problem-solving. The study concludes that using Funny Blocks significantly enhances students’ understanding of rectangular prism geometry compared to conventional methods. Therefore, this teaching aid is recommended as an innovative learning medium to improve the quality of mathematics education in elementary schools.